2021
DOI: 10.1101/2021.08.18.21262237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Delta on viral burden and vaccine effectiveness against new SARS-CoV-2 infections in the UK

Abstract: The effectiveness of BNT162b2, ChAdOx1, and mRNA-1273 vaccines against new SARS-CoV-2 infections requires continuous re-evaluation, given the increasingly dominant Delta variant. We investigated the effectiveness of the vaccines in a large community-based survey of randomly selected households across the UK. We found that the effectiveness of BNT162b2 and ChAd0x1 against any infections (new PCR positives) and infections with symptoms or high viral burden is reduced with the Delta variant. A single dose of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 33 publications
5
85
1
Order By: Relevance
“…Serial assessment for infection in British households suggests high vaccine induced protection against SARS-CoV-2, including the dominant variant of concern B.1.1.7 or alpha during the fourth wave of infection in spring 2021. More, recently there has been some erosion in VE SUSC associated with the predominance of B.1.167.2 or delta [6]. While not providing a precise estimate of VE SUSC , these data suggest that at least some observed efficacy against disease in clinical trials is mediated by complete protection against infection.…”
Section: Vaccine Efficacy Against Transmissability Given Infectionmentioning
confidence: 88%
See 2 more Smart Citations
“…Serial assessment for infection in British households suggests high vaccine induced protection against SARS-CoV-2, including the dominant variant of concern B.1.1.7 or alpha during the fourth wave of infection in spring 2021. More, recently there has been some erosion in VE SUSC associated with the predominance of B.1.167.2 or delta [6]. While not providing a precise estimate of VE SUSC , these data suggest that at least some observed efficacy against disease in clinical trials is mediated by complete protection against infection.…”
Section: Vaccine Efficacy Against Transmissability Given Infectionmentioning
confidence: 88%
“…Five VE SUSC and VE SYMP combinations (5 × 3 or 15 scenarios when considering the 3 values of VE INF ): VE SUSC = 90%/VE SYMP = 10%; VE SUSC = 10%/VE SYMP = 90%; VE SUSC = 90%/VE SYMP = 50%; VE SUSC = 50%/VE SYMP = 90%; VE SUSC = 90%/VE SYMP = 90%) would be compatible with current projections for the Moderna and Pfizer mRNA vaccines against B.1.1.7 which had estimated VE DIS = 95% and 90%, respectively [4,5]. Three combinations or nine scenarios (VE SUSC = 50%/VE SYMP = 50%; VE SUSC = 50%/VE SYMP = 10%; VE SUSC = 10%/VE SYMP = 50%) would be realistic if there is a relative decrease in VE DIS due to new viral variants as appears to be occurring with the now predominant B.1.617.2 variant of concern [6]. These lower vaccine estimates may also be relevant for other vaccines in development, or after a single dose of the Moderna or Pfizer product.…”
Section: Vaccine Simulations In King County Washingtonmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular concern currently is the Delta variant that is spreading globally, as recent data suggests that both the AstraZeneca and Pfizer vaccines are slightly less effective against this variant in preventing COVID-19 related symptoms compared to the Alpha variant [75]. A recent large-scale study of Delta infections in the UK found that the protection offered against the variant by the AstraZeneca and Pfizer vaccines wanes with time, further supporting the need for variant-specific vaccines to boost immunity against variants of concern [76]. Despite global vaccination efforts, the rise in COVID-19 cases around the world as the Delta variant of SARS-CoV-2 spreads implies that variant-specific booster shots may be needed to combat emerging variants.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only a slight decline was observed in preventing severe disease and its consequences 20,21 . Considering differential effectiveness against the Delta variant, reports vary substantially as to whether, and to what extent, the vaccine is effective in reducing viral loads of BTI with the Delta variant 8,[22][23][24][25][26][27][28][29][30][31][32] .…”
mentioning
confidence: 99%